Single-use flexible ureteroscopes: practice patterns, attitudes, and preferences for next-generation concepts - Salka, Bassel; Bahaee, Jamsheed; DiBianco, John Michael; Plott, Jeff; Ghani, Khurshid R. (Frontiers in Surgery, 2024)
Background: Single use flexible ureteroscopes (su-fURS) have emerged as an alternative to reusable flexible ureteroscopes (r-fURS) for the management of upper urinary tract calculi. However, little is known about urologist usage and attitudes about this technology. Through a worldwide survey of endourologists, we assessed practice patterns and preferences for su-fURS.Methods: An online questionnaire was sent to Endourology Society members in January 2021.The survey explored current su-fURS practice patterns, reasons for/against adoption, and preferences for next generation models including developments in imaging, intra-renal pressure, heat generation, and suction. Responses were collected through QualtricsXM over a 1-month period from surgeons in North America, Latin America, Europe, Asia, Africa, and Oceania. The study was conducted according to the Checklist for Reporting Results of Internet E-Surveys (CHERRIES).Results: 208 (13.9%) members responded to the survey. Most respondents (53.8%) performed >100 ureteroscopies per year. 77.9% of all respondents used su-fURS for less than half of all procedures while only 2.4% used su-fURS for every procedure. 26.0% had never used a su-fURS. Overall, usage was not influenced by a surgeon's geographic region, practice environment, or years of experience. Top reasons for not adopting su-fURS were cost (59.1%) and environmental impact (12.5%). The most desired improvements in design were smaller outer shaft size (19.4%), improved optics and vision (15.9%), and wireless connectivity (13.6%). For next generation concepts, the functions most commonly described as essential or important by respondents was the ability to suction fragments (94.3%) while the function most commonly noted as not important or unnecessary was incorporation of a temperature sensor (40.4%).Conclusions: su-fURS are not commonly used, even among urologists who perform a high number of fURS. The primary concern for adoption is cost and environmental impact. Suction capability was considered the most important future development.